FROM GUT TO MIND: THE INFLUENCE OF MICROBIOTA COMPOSITION ON POSTPARTUM DEPRESSION - Marta Czarnowska; Radosław Sciepuro; Nina Czarnowska; Layla Settaf-Cherif; Katarzyna Malinowska; Joanna Barwacz; Magdalena Adamik; Dagmara Gładysz; Agnieszka Zaleszczyk (International Journal of Innovative Technologies in Social Science, 2025)
Background: Postpartum depression is a significant mood disorder affecting women during the first year after childbirth. Emerging evidence indicates that gut microbiota may play a meaningful role in its development through inflammatory, metabolic, and neuroendocrine pathways. The purpose of this review is to synthesize current knowledge on gut microbiota alterations during pregnancy and postpartum and to evaluate their potential contribution to postpartum depression, with emphasis on mechanistic links and opportunities for therapeutic modulation. Methodology: This review was conducted by analyzing clinical, mechanistic, and translational studies, using PubMed, the Cochrane Library, and Google Scholar databases, that focused on maternal microbiota composition, postpartum mood disturbances, and microbiota-modulating strategies. Results: The reviewed evidence demonstrates that women with depressive symptoms commonly exhibit reduced levels of anti-inflammatory and short-chain-fatty-acid-producing bacteria and an increased presence of pro-inflammatory taxa. Pregnancy and postpartum are characterized by substantial microbial shifts, including changes in Firmicutes and Bacteroidetes, with postpartum reductions in beneficial genera such as Faecalibacterium and Bacteroides. These alterations may influence inflammation, neurotransmitter metabolism, intestinal barrier function, and stress-axis activity, collectively contributing to depressive risk. Interventions aimed at modulating the maternal microbiota, including dietary strategies and probiotic supplementation, show preliminary potential for reducing depressive symptoms or lowering postpartum depression risk. Conclusions: Overall, current findings suggest that gut microbiota may represent both a biomarker and a modifiable factor in postpartum depression. Microbiota-targeted approaches warrant further investigation to determine their preventive and therapeutic utility in maternal mental health.